2011
DOI: 10.1007/s10995-011-0868-8
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Pollutants and Racial/Ethnic Disparity in Feto-Infant Morbidity Outcomes

Abstract: We sought to assess the association between air particulate pollutants and feto-infant morbidity outcomes across racial/ethnic subgroups. This is a retrospective cohort study from 2000 through 2007 based on three linked databases: (1) The Florida Hospital Discharge database; (2) The vital statistics records of singleton live births in Florida; (3) Air pollution and meteorological data from the Environmental Protection Agency. Using computerized mathematical modeling, we assigned exposure values of the air poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 22 publications
4
49
0
1
Order By: Relevance
“…In contrast, a recently published study using particulate air pollutant data in Florida from 2000 to 2007 found an overall increased risk of PTB (OR: 1.12, 95% CI: 1.06-1.18), low-birth-weight (OR: 1.18, 95% CI: 1.11-1.25) and very-low-birth-weight deliveries (OR: 1.27, 95% CI: 1.08-1.49) in the 23.2% of total births that lived in a particulate exposed area. When the effect of exposure to particulate air pollution was examined in non-Hispanic white and black women separately, exposure to air pollution in black women was associated with a 68-300% higher increase odds of these adverse outcomes compared to white women exposed to particulate air pollution (61).…”
Section: Physical Environmentmentioning
confidence: 99%
“…In contrast, a recently published study using particulate air pollutant data in Florida from 2000 to 2007 found an overall increased risk of PTB (OR: 1.12, 95% CI: 1.06-1.18), low-birth-weight (OR: 1.18, 95% CI: 1.11-1.25) and very-low-birth-weight deliveries (OR: 1.27, 95% CI: 1.08-1.49) in the 23.2% of total births that lived in a particulate exposed area. When the effect of exposure to particulate air pollution was examined in non-Hispanic white and black women separately, exposure to air pollution in black women was associated with a 68-300% higher increase odds of these adverse outcomes compared to white women exposed to particulate air pollution (61).…”
Section: Physical Environmentmentioning
confidence: 99%
“…9 And, although socioeconomic and racial disparities in infant health outcomes are well documented and disadvantaged groups may be exposed to higher levels of pollution, the potential confounding effects of demographic factors on the association between infant health and air pollution are not well understood. One noteworthy study by Salihu et al, 11 using the same data set, demonstrated that in women exposed (values more than median) to particulate matter 10 (PM 10 ) and particulate matter 2.5 (PM 2.5 ), there was an increased rate of LBW, very lowbirth-weight and preterm birth (PTB) outcomes. African American women had the greatest odds for all morbidity outcomes, with the greatest relationship to very low-birth-weight infants.…”
mentioning
confidence: 99%
“…African American women had the greatest odds for all morbidity outcomes, with the greatest relationship to very low-birth-weight infants. 11 Accordingly, we undertook this study to assess the impact of exposure to particulate matter (PM 10 3 and Pb on fetal morbidity by using a more complex but accurate model that takes into account latent variables and multiple analysis. Structural equation modeling (SEM) is a statistical analysis technique that permits simultaneous analysis of multiple factors whose true effects on an outcome cannot be assessed independently because of a lack of independent natural occurrence.…”
mentioning
confidence: 99%
“…[35][36][37][38] A study conducted in California examined racial/ethnic disparities in cardiovascular and respiratory hospital admissions and asthma emergency room visit rates resulting from exposure to ozone and PM 2.5 concentrations in excess of federal standards. 36 This study used zip code-level daily average air pollution exposures and hospital event rates from state databases to calculate excess attributable risk over 2005-2007 for Caucasian-American, African-American, Hispanic and Asian/Pacific Islander residents by zip code and found that for cardiovascular admissions African-American residents experienced significantly higher excess attributable risk compared with Caucasian-American residents, and Hispanic and Asian/Pacific Islander residents experienced significantly lower excess attributable risk compared with Caucasian-American residents; this study, however, did not evaluate air pollution exposure as a mediator of the association between race/ethnicity and hospital event rates.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of air pollution with disparities in other health outcomes have been limited to ecological exposure assessment, lack of adjustment for relevant risk factors and self-reported study outcomes, especially for cardiovascular disease. [35][36][37][38] The objective of this study was to estimate the influence of exposure to PM 2.5 and NO X , estimated at the household level, to racial/ethnic differences in carotid IMT. Given the higher air pollution exposure among non-Caucasian-American individuals (especially Chinese Americans) compared with Caucasian-American individuals, 18 and the positive association between air pollution and IMT, [30][31][32][33][34] we hypothesised that accounting for exposure to ambient air pollution would result in smaller IMT levels for African-American, Hispanic and Chinese participants compared with Caucasian-American participants.…”
Section: Introductionmentioning
confidence: 99%